A consecutive case review of token systems used to reduce socially maintained challenging behavior in individuals with intellectual and developmental delays. (2nd July 2016) - Scheithauer, Mindy; Cariveau, Tom; Call, Nathan A.; Ormand, Hailey; Clark, Seth
Abstract : Objectives: The current paper describes the use of token systems in a behavioral day-treatment unit for severe challenging behavior using a consecutive case review spanning three years. Methods: Experimenters reviewed 96 patient case files, 24 of which implemented some token system as a component of the individual's treatment package. Aspects of each token system (including schedules of token delivery and exchange; inclusion of token training and response cost; and types of backup reinforcers delivered), and participant characteristics were coded. Results: Token systems were most frequently employed during differential reinforcement for alternative behavior (DRA, most commonly for compliance) or differential reinforcement of other behavior (DRO). Tokens were most frequently used in an instructional context. Several commonalities were identified (e.g. restriction of backup reinforcers between token exchanges and initial dense schedules of reinforcement). Compared to past reviews, this sample had an over-representation of individuals with challenging behavior maintained by escape, multiply maintained challenging behavior, and individuals for which the function was not identified in a functional analysis. Treatment packages including token systems resulted in a reduction in challenging behavior for 91.67% of participants, with 70.83% exhibiting at least an 80% reduction. Conclusion: Our findings suggest that token systems may be a beneficial component of treatment plans used to address challenging behavior. Some common components should likely be included in all token systems and specific client variables may guide decisions related to idiosyncratic treatments.